Lamenting the Loss of the Local - Kelen, Christopher (LiNQ (Literature in North Queensland), 2016)
Macao is—a city in south China, a Special Administrative Region of the People’s Republic, the last of Europe’s colonial possessions to be returned in the Far East, the region’s only city with casinos, a mere dot on the map. And yet this 28 square kilometers (at the time of writing), current population 600,000, among other things, the world’s most crowded territory, has historical and geo-political importance far outstripping the first impression given by this collection of facts. That importance has to do with Macao’s various kinds of uniqueness, for instance in intercultural terms, and as the only place in China where gambling is legal. This latter fact has powered Macao’s twenty-first century transformation from sleepy backwater into the Vegas of the East - a casino capitalist sponge for some of China’s new wealth. One might say that its dot-on-the-map status makes Macao capable of bearing the symbolic burden that goes along with having been for several hundred years the principal portal between China and West, that goes along with being the last of the East Asian colonies returned. It’s the dot-on-the-map status as well that makes Macao seem an unthreatening place in which to isolate acknowledged vices (of the kind for which it has long been famous).